Insights into gated electron-transfer kinetics at the electrode-protein interface: A square wave voltammetry study of the blue copper protein azurin - Jeuken, L; McEvoy, J; Armstrong, F (2002)
The rapid electron-transfer reaction of the blue copper protein azurin adsorbed on different electrodes (pyrolytic graphite "edge" (PGE) and gold modified with self-assembled monolayers of various 1-alkanethiols) has been studied by cyclic and square ware voltammetry. By using large values (0.075-0.3 V) for the square wave amplitude, the electron-transfer (ET) rate is measured over a continuously variable driving force in either direction. Values for k 0 (the standard ET "exchange" rate constant at zero driving force) depend on the nature of the electrode; by contrast, k max (the maximum rate constant at high driving force) is essentially invariant with a rate of (6 ± 3) × 10 3 s -1 at 0 °C for both oxidation and reduction, irrespective of whether the electrode is PGE or Au modified with either dodecanethiol or decanethiol. Using Marcus theory, the potential dependences yield an extremely low value for the reorganization energy (λ < 0.25); however, a good fit is obtained with an alternative model in which ET is gated by a preceding process that is common to all cases. The nature of this limitation has been probed by varying pH, H 2O vs D 2O, solvent viscosity, and temperature. There is little dependence on medium, thereby ruling out proton transfer or major (translational) motion in the ET-limiting step. The temperature dependences for both PGE (-40 to 0 °C) and gold (0-50 °C) electrodes give good fits to the Arrhenius equation, with activation energies E A = 19.5 ± 1.1 and 2.6 ± 1.7 kJ mol -1, respectively. Consequently, the gating process has an unfavorable activation entropy, suggesting that electron transfer is dependent upon prior formation of a highly ordered protein configuration on the electrode surface.